Increased planting density of Chinese milk vetch (Astragalus sinicus) weakens phosphorus uptake advantage by rapeseed (Brassica napus) in a mixed cropping system. Issue 4 (22nd June 2019) - Zhang, Deshan; Li, Hongbo; Fu, Zishi; Cai, Shumei; Xu, Sixin; Zhu, Haitao; Shen, Jianbo
Abstract: Neighbouring plants can affect plant growth through altering root morphological and physiological traits, but how exactly root systems respond to neighbouring plants with varied density, determining nutrient uptake and shoot growth is poorly understood. In a pot-based experiment, rapeseed was grown alone (single rapeseed), or mixed with 3, 6, or 15 Chinese milk vetch plants. As controls, monocropped Chinese milk vetch was grown at the same planting density, 3, 6, or 15 plants per pot. Root interaction between rapeseed and Chinese milk vetch facilitated phosphorus (P) uptake in rapeseed grown with 3 plants of Chinese milk vetch. As the planting density of Chinese milk vetch in mixture increased, there was a decrease in citrate concentration and acid phosphatase activity but an increase in the total root length of Chinese milk vetch per pot, resulting in decreases in rapeseed root biomass, total root length and P uptake when rapeseed was grown with 6 or 15 Chinese milk vetch plants relative to rapeseed grown with 3 plants. These results demonstrate that the enhanced nutrient utilization induced by root interaction at low planting densities was eliminated by the increased planting density of the legume species in rapeseed/Chinese milk vetch mixed cropping system, suggesting that root/rhizosphere management through optimizing legume planting density is important for improving crop productivity and nutrient-use efficiency. Abstract : The positive effects induced by neighbouring legumes on nutrient uptake depended on the legume planting density in a mixed cropping system. In rapeseed/Chinese milk vetch system, the Chinese milk vetch at low planting density had a small root system but high levels of citrate and acid phosphatase exudation, thus facilitating rapeseed phosphorus (P) uptake; as the Chinese milk vetch planting density increased, there was a decrease in rapeseed P uptake due to the reduction in root exudation but root-size increase in Chinese milk vetch. Optimizing legume planting density is important for improving nutrient-use efficiency in mixed cropping system with legumes.